Garabato, the Sensible Cat (2010)
The theater rplay: “Socrates. On Violeta's Dreams and Garabato's Adventures ”was presented for the first time at EAFIT on October 9, 2010. More than 300 children and young people attended the event and got close to these interesting characters who introduced them to Socrates, the Greek philosopher that with questions and dialogues invites to reflection.